EU SOCIAL INCLUSION POLICY AND THE PROGRESS OF THE HOMELESS POLITICS IN BALTIC STATES. ANALYSIS OF THE NATIONAL ACTION PLANS OF SOCIAL INCLUSION - Kõre, Jüri; Karpuškiene, Vita (Socialinė teorija, empirija, politika ir praktika, 2009)
The article we would like to present is a part of the research carried out in cooperation with FEANTSA (the European Federation of National Organizations Working with the Homeless) and national social agencies. The aim of the article is to explain and describe the institutional and cultural changes taking place in the context of the so called "double" transition process that was observed in the Baltic States Central - and East - European (CEE) countries at the end on the 1980s. Parallel processes that can be recognized in the context of the development of anti-poverty politics at the national and supranational (EU) level will also be described and explored in the given paper. The purpose of the given analysis is the following: 1. To describe general differences in the social protection system of the Baltic States, with a focus on housing politics; 2. To analyze homelessness as a form of European Union's social inclusion politics in national politics, using NAP-s (National Action Plan Against Poverty and Social Exclusion).
Keywords: Homeless; Anti-poverty policy; Comparative research; Baltic States